Cost-effectiveness of case-based training for primary care physicians in evidence-based medicine of patients with coronary heart disease. (March 2016) - Groot-Jensen, Susanne; Kiessling, Anna; Zethraeus, Niklas; Björnstedt-Bennermo, Marie; Henriksson, Peter
Background: We have shown that a case-based training programme for general practitioners, aimed to implement evidence-based care of patients at very high risk of coronary death, was associated with decreased mortality. In the present study we assessed long-term cost-effectiveness of this programme. Design: Registry-based long-term cost-effectiveness analysis on a clinical trial. Methods: Costs of the programme, health care, drugs and added years of life were included. Costs were adjusted to 2012 level and discounted by 3%. Life-years gained were estimated as the difference between the survival curves of the trial. The effectiveness measure, quality adjusted life-years (QALYs), was constructed by multiplying each life-year with a quality of life weight corresponding to the health status of that year. QALYs were also discounted by 3%. Incremental cost-effectiveness ratio (ICER) was estimated as the incremental cost per QALY gained. Results: The number of undiscounted life-years gained was 365 days in the intervention group as compared to control ( p  = 0.02). The number of discounted QALYs gained was 0.66. The net increase in total costs was estimated as 17, 862 € when costs of added years of life were included and 4621 € exclusive of these costs. This implied an ICER of 27, 063 € per gained QALY. This ICER is well below commonly used threshold values of the societal willingness to pay for a QALY. Conclusions: The results show that a case-based training programme of general practitioners is a cost-effective way to save years of life in patients with very high risk of coronary death.